Indonesian Men's Perceptions of Violence Against Women. (July 2014) - Nilan, Pam; Demartoto, Argyo; Broom, Alex; Germov, John
This article explores male perceptions and attitudes toward violence against women in Indonesia. It analyzes interview data from Indonesian men collected as part of a large multimethod Australian government–funded project on masculinities and violence in two Asian countries. Reluctance to talk about violence against women was evident, and the accounts of those men who did respond referred to three justificatory discourses: denial, blaming the victim, and exonerating the male perpetrator. The findings support continuation of government and nongovernmental organization (NGO) projects aimed at both empowering women and reeducating men.